Contributions to the taxonomy of the genus Hylaeus in India, with an identification key and a new species (Hymenoptera: Colletidae). (3rd April 2022) - Saini, Jagdish; Chandra, Kailash; Kumar, Hirdesh
ABSTRACT: A new species Hylaeus ( Paraprospis ) guptai Saini & Chandra sp. nov ., is described from Jang (Arunachal Pradesh), India. Specimens were collected from flowers of Coriander ( Coriandrum sativum L.) during April 2018. In addition, Braunsapis chandrai syn. nov . is recognised as synonym of Hylaeus ( Indialaeus ) strenuus . A key and a checklist of Hylaeus species from India is provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:7139F2C9-FF8D-49CB-9911-1CCABD9E72C2